Decolonisation - White, Nicholas J (Seminar studies, 2014)
This updated Seminar Studies volume provides an overview of the process of British decolonisation. The eclipse of the British empire has, of course, been one of the central features of postwar international history. At the end of the Second World War the empire still spanned the globe and yet by the mid-1960s most of Britain's major dependencies had achieved legal independence. Concisely and accessibly, Nicholas White introduces students to this often dramatic story of colonial wars and emergencies, and fraught international relations.